From eco-anxiety to eco-hope: surviving the climate change threat - Betro’, Sophia (Frontiers in Psychiatry, 2024)
Introduction -As the average global temperature increases, the effects of climate change worsen, through effects on worsening extreme events as well as exacerbating political, economic, social turmoil (wars, conflicts and migrations). This poses an existential risk to the survival of humans and nonhumans. These effects are visible due to the impact on people's mental health and psychophysical wellbeing. This article aims to explores the growing phenomenon of psychoterratic syndromes, with focus on the effect of ecoanxiety on mental health. Furthermore, is outlined the relationship between ecoanxiety and behavior response (both individual and collective) in the climate crisis era.Methods -A research with interdisciplinary approach was carried out for recent literature and articles relating to psychoterratic syndromes and the effects of climate change on mental health.research on the onset of new emotions in response to psychological effects to climate change, called psychoterratic syndromes (such as ecoanxiety, climate anxiety, solastalgia, ecogrief etc.). Among these, eco-anxiety is the most popular term used for describe how people feel about climate change. However, the paradigm that described ecoanxiety only as a pathological emotion need to be changed. Discussion -The article emphasizes the positive effect of eco-emotions and the need to stimulate people to move from a state of anxiety, which could bring apathy and resignation, towards eco-hope. Eco-hope could be an adaptive coping mechanism in people and communities, which is key to preventing, mitigating and protecting mental and planetary health.